Effectiveness of Convalescent Plasma Therapy in Treating COVID-19: an Evidence-based Case Report - Mira Yulianti; Christian Johan; Gurmeet Singh; Eric Daniel Tenda; Herikurniawan Herikurniawan; I Putu Eka Krisnha Wijaya (Interna Publishing, 2022)
Background: Convalescent plasma is a potentially beneficial, tolerable, and available additional treatment option for COVID-19. This study aims to evaluate whether the administration of convalescent plasma therapy leads to improved clinical outcomes in COVID-19 patients compared to standard medical therapy. Methods: We conducted a search of Pubmed, Cochrane, and EBSCO for studies assessing the clinical question using inclusion and exclusion criteria. Selected studies were critically appraised, and the results were summarized. Results: A meta-analysis of 10 randomized clinical trials (RCTs), an RCT, a case-control clinical study were selected and assessed. Only the case-control clinical study showed that convalescent plasma administration improved the clinical outcomes of patients with COVID-19, including all-cause mortality, hospital length of stay, and the need for mechanical ventilation. On the contrary, the other two studies of a higher level of evidence showed no significant clinical outcome improvement with convalescent plasma therapy. Conclusion: The effectiveness of convalescent plasma therapy in improving clinical outcomes of patients with COVID-19 was still inconclusive due to several study limitations and other possible causes.